Ex Vivo Chemosensitivity Profiling of Acute Myeloid Leukemia and Its Correlation With Clinical Response and Outcome to Chemotherapy - Zhang, Yi; Ji, Min; Zhao, Jin-Yan; Wang, Hua-Feng; Wang, Chong-Wu; Li, Wei; Ye, Jing-Jing; Lu, Fei; Lin, Li-Hui; Gao, Yan-Ting; Jin, Jie; Li, Li; et al. (Frontiers in Oncology, 2022)
We evaluated the predictive value of the ex-vivo PharmaFlow PM platform in measuring the pharmacological activity of drug combinations consisting of 20 different chemotherapy regimens (20 Tx) administered in 104 acute myeloid leukemia (AML) patients. The predicted sensitivities of alternative treatments for each patient were ranked in five 20% categories, from resistant to sensitive (Group 1–5). The complete remission (CR) rate of the five groups was 0%, 12.5%, 38.5%, 50.0%, 81.3%, respectively. The heat map showed a good relationship between drug sensitivity with CR (Group 4+5 vs Group 1+2+3：77.5% vs. 27.3%, p=0.002) and the European Leukemia Net risk group (22.6% vs. 63.6%, p=0.015). The predicted coincidence rate was 90.9% in Group 1+2 and 81.3% in Group 5. According to the recommendations of the PharmaFlow PM platform, the CR rate would have increased about 16.3% in one cycle. The overall survival (OS) was shorter in patients predicted to be resistant (Group 1+2 vs Group 3+4+5, p=0.086). In multivariable analysis, CR after one cycle was an independent prognostic factor for OS (P=0.001; 95% CI 0.202 (0.080–0.511)), and ex-vivo chemosensitivity was a potential predictive factor for OS (p=0.078; 95% CI 0.696 (0.465–1.041)). To conclude, the PharmaFlow PM platform is a rapid and valuable tool for predicting clinical response and outcomes in AML patients.